Regenerative agriculture as a biomimetic technology. (March 2022) - Gremmen, Bart
As populations increase and economic affluence expand, conventional farmers will be unable to meet the demand for food. Two main scenarios offer different solutions. The first scenario aims to further intensify scientific- and technology-driven agriculture research. The second scenario aims to radically switch to nature-based solutions in agricultural systems. There seem to be two interpretations of the nature-based solutions scenario: on the one hand, the interpretation of the IUCN regards nature-based solutions, such as regenerative agriculture, as using nature and denies a link with biomimicry; and on the other hand, the interpretation of the EU regards regenerative agriculture as an example of biomimicry. This raises the question: is regenerative agriculture a prime example of biomimicry or is it only a very important way to use nature in agriculture? To answer this question, we take a step back and philosophically reflect on biomimicry. Based on two definitions of mimesis, we distinguish between two concepts of biomimicry, a 'strong' concept which emphasizes natural principles and copying natural models, and a 'weak' concept, which emphasizes inspiration by nature and creative invention. Secondly, we describe and analyze regenerative agriculture as part of the nature-based solutions scenario and interpret regenerative agriculture first as 'weak' and then as 'strong' biomimicry. Both interpretations have their problems. To address these, we propose a new concept of biomimicry based on a new definition of mimesis. This enable us to differentiate between biomimicry, strict imitation of nature, and nature-inspired invention. We argue that our conceptualization of biomimicry helps to operationalize regenerative agriculture as a biomimetic technology.